PENGARUH ABU TERBANG BATUBARA, KOMPOS TANDAN KOSONG KELAPA SAWIT, DAN MIKORIZA TERHADAP KETERSEDIAAN DAN SERAPAN FOSFOR, PERTUMBUHAN DAN PRODUKSI JAGUNG PADA ULTISOL - Laili Fahimatul Mashfufah; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Ultisol has limitation to become agricultural land by low soil pH, high saturation of Al, poor macronutrients and low organic matter content. Maize production in Ultisol is faced with a lack of P. The purpose of this study was to determine the effect of coal fly ash (CFA), oil palm empty fruit bunch (OPEFB) and mycorrhiza to help increase the availability and uptake of phosphorus, growth and production of corn on Ultisol. The combination consisted of twelve treatments with 3 replications. The research was conducted in a glasshouse by planting corn on the planting media according to the treatment. Plant height and number of leaves were observed every week, at harvest (age 13 weeks) observed fresh weight and dry weight of shoot + root, fresh weight of cob with cornhusk, fresh weight of cob, weight of shelled seeds, production. P-total, P-available, P uptake, soil pH, organic-C, number of spores and percentage of root colonies were observed in the laboratory. The application of the combination of CFA and OPEFB and mycorrhiza did not have a significant effect on total-P, available-P, soil pH, organic-C, plant height, number of leaves, dry weight of shoot + root, fresh weight of cob with cornhusk and weight of shelled seeds. CFA, OPEFB and mycorrhiza influential in increasing P-uptake, dry weight of shoot + root, fresh weight of cob, production, number of spores and percentage of root colonies